THE FAMOUS SCIENTIST G. I. MARCHUK, the Last President of the USSR Academy of Sciences, a Foreign Member of Georgian Academy of Sciences, is 85 Years Old - Lominadze, Jumber G.; Kordzadze, Avtandil A. (Journals of Georgian Geophysical Society, 2017)
A famous scientist in the field of calculus and applied mathematics, a great organizer of science, a good teacher, a Hero of Socialist Labour, a Laureate of Lenin and State Awards, Academician, GuriIvanovich Marchuk is 85 years old. Nowadays GuriIvanovich is known in the world as one of great scientists, which has dedicated all his scientific work to the studies in the field of calculus and applied mathematics, methods of nuclear reactors, atmosphere and ocean physics, mathematical modeling of the problems of the environment, modeling in immunology and medicine, information and computer sciences.